2014
DOI: 10.1088/0004-637x/798/1/41
|View full text |Cite
|
Sign up to set email alerts
|

The Near-Ultraviolet Luminosity Function of Young, Early M-Type Dwarf Stars

Abstract: Planets orbiting within the close-in habitable zones of M dwarf stars will be exposed to elevated high-energy radiation driven by strong magneto-hydrodynamic dynamos during stellar youth. Nearultraviolet (NUV) irradiation can erode and alter the chemistry of planetary atmospheres, and a quantitative description of the evolution of NUV emission from M dwarfs is needed when modeling these effects. We investigated the NUV luminosity evolution of early M-type dwarfs by cross-correlating the Lépine & Gaidos (2011) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 74 publications
5
43
0
Order By: Relevance
“…There is an increase of flux density with effective temperature in both GALEX bands with young (≤300 Myr) stars emitting more emission than older stars. These trends are consistent with the work of and Ansdell et al (2015), who used averaged GALEX flux densities. Despite later M stars showing more variability (in the NUV), they emit less excess UV emission in both GALEX bands.…”
Section: Galex Fuv and Nuv Correlations And Ratiossupporting
confidence: 91%
“…There is an increase of flux density with effective temperature in both GALEX bands with young (≤300 Myr) stars emitting more emission than older stars. These trends are consistent with the work of and Ansdell et al (2015), who used averaged GALEX flux densities. Despite later M stars showing more variability (in the NUV), they emit less excess UV emission in both GALEX bands.…”
Section: Galex Fuv and Nuv Correlations And Ratiossupporting
confidence: 91%
“…The fastest rotator of our example stars (P rot ∼ 1 d) falls into the saturated regime of the near-UV activity-age relation ( Fig. 13 of Ansdell et al 2015), which indicates an age < 160 Myr, while the other fast rotator (P rot ∼ 6 d) shows a near-UV excess emission consistent with a Hyades age (approximately the age of Praesepe). The flare data of Ilin et al (2019) of the Pleiades are therefore inconsistent with our FFD measurements.…”
Section: Discussionmentioning
confidence: 67%
“…Based on this, the two fast-rotating mid-M dwarfs that we show as examples might be young. For these two stars, Ansdell et al (2015) found significant near-UV excess emission. The fastest rotator of our example stars (P rot ∼ 1 d) falls into the saturated regime of the near-UV activity-age relation ( Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Here, we find that our object appears to lie between the active and inactive loci and that while it does not have a far-UV detection, it could have emission above Shkolnik et al (2009)'s F NUV /F J > 10 −5 and still remain undetected by GALEX. However, the near-UV emission is of little use as Ansdell et al (2014) noted that the fully convective transition in mid-M dwarfs makes it impossible to define a near-UV inactive locus of M dwarfs beyond M3. Hence, we do not consider 2MASS J0213+3648 AB's near-UV emission to be a reliable age diagnostic.…”
Section: The Age Of 2mass J0213+3648 Abmentioning
confidence: 99%